Dynamic remodeling of endometrial extracellular matrix regulates embryo receptivity in cattle. Issue 1 (January 2017) - Scolari, Saara Carollina; Pugliesi, Guilherme; Strefezzi, Ricardo de Francisco; Andrade, Sónia Cristina da Silva; Coutinho, Luiz Lehmann; Binelli, Mario
Abstract : We aimed to evaluate in the bovine endometrium whether (1) key genes involved in endometrial extracellular matrix (ECM) remodeling are regulated by the endocrine peri-ovulatory milieu and (2) specific endometrial ECM-related transcriptome can be linked to pregnancy outcome. In Experiment 1, pre-ovulatory follicle growth of cows was manipulated to obtain two groups with specific endocrine peri-ovulatory profiles: the Large Follicle-Large CL group (LF-LCL) served as a paradigm for greater receptivity and fertility and showed greater plasma pre-ovulatory estradiol and post-ovulatory progesterone concentrations compared to the Small Follicle-Small CL group (SF-SCL). Endometrium was collected on days 4 and 7 of the estrous cycle. Histology revealed a greater abundance of total collagen content in SF-SCL on day 4 endometrium. In Experiment 2, cows were artificially inseminated and, six days later, endometrial biopsies were collected. Cows were retrospectively divided into pregnant and non-pregnant (P vs NP) groups after diagnosis on day 30. In both experiments, expression of genes related to ECM remodeling in the endometrium was studied by RNAseq and qPCR. Gene ontology analysis showed an inhibition in the expression of ECM-related genes in the high receptivity groups (LF-LCL and P). Specifically, there was downregulation of TGFB2, ADAMTS2, 5 and 14, TIMP3 and COL1A2, COL3A1, COL7A1 and COL3A3 in the LF-LCL and P groups. In summary, the overlapping set of genes differently expressed in both fertility models: (1) suggests that disregulation of ECM remodeling can impair receptivity and (2) can be used as markers to predict pregnancy outcome in cattle.